Analysis of the financial management of micro and small companies in the retail sector in the City of Cláudio (Research, Society and Development, 2020)
Working capital are financial resources that fund the company's operating activities. Its efficient management provides increased profitability, liquidity and longevity for organizations. Micro and small companies - MPEs are important for the Brazilian socioeconomic development, generating jobs and income. The objective of this work was to analyze the main factors that influence the working capital management of Cláudio's retail MSEs. A descriptive research with a quantitative approach was carried out. Data were collected by applying a questionnaire to an intentional sample of 38 companies. It was found that the companies had been in the market for more than 10 years. The partners did the financial management of the enterprise, were male and had worked in finance for over 10 years. A large part had a college degree, another significant part had only completed high school, few had technical knowledge of finance. The companies had sufficient capital to make payments. They had cash control, banks, accounts receivable, sales and defaults. They calculated the average payment term and did financial planning. The main difficulties in financial management were using more useful tools to increase profit, analyzing the financial statements, implementing a Management Information System, making provision for vacation payments, thirteenth salary and carrying out inventory control. The hypothesis was confirmed, as the financial managers, because they have little technical knowledge of the area, did not have the necessary skills for a more efficient management of working capital.